Policing with a public health lens – Moving towards an understanding of crime as a public health issue. (September 2022) - Bucerius, Sandra M; Oriola, Temitope B; Jones, Daniel J
Policing organizations are currently experiencing more pressure than ever to address systemic racism and police brutality. Advocates and academics have suggested a range of changes, such as defunding the police, moving towards more body-worn cameras, ensuring higher educational levels of new recruits, implicit bias training, and so on. Our article draws attention and advocates for a different avenue: moving our understanding of crime towards a public health issue. By drawing on some data from the University of Alberta Prison Project, we argue that looking at justice clients with a public health lens would significantly change the way police are trained and respond to incidents. We believe this would have monumental consequences for both justice clients and policing organizations: justice clients will benefit from a police service that is trauma informed, compassionate, and understands their client base, while policing organizations will arguably increase their trust relationship with the public, therefore building legitimacy in the community.